Microbial Enhanced Oil Recovery: Literature Review - Ulfah, Baiq Maulinda; Fathaddin, Muhammad Taufiq; Setiati, Rini (Sekolah Tinggi Teknologi MIGAS, 2024)
The demand for fossil fuels continue to increase, this encourages the production of hydrocarbons to be increased as well. Enhanced Oil Recovery is one option that can be considered to overcome this high demand. Technical complexity and sophisticated technology are commonly used in EOR implementation. This has become one of the obstacles to implement EOR, one of which is the requirement relatively large funding. Microbial Enhanced Oil Recovery is one method that can be considered as a technology that can fulfill commercial production gains and the resulting environmental impact is lower than other EOR methods. MEOR uses micro-organisms whose metabolism results can change the physical properties in the reservoir so that oil production can be increased.